Quality Attestation for Clinical Ethics Consultants: A Two‐Step Model from the American Society for Bioethics and Humanities. (1st October 2013) - Kodish, Eric; Fins, Joseph J.; Braddock, Clarence; Cohn, Felicia; Dubler, Nancy Neveloff; Danis, Marion; Derse, Arthur R.; Pearlman, Robert A.; Smith, Martin; Tarzian, Anita; Youngner, Stuart; Kuczewski, Mark G.
Abstract: Clinical ethics consultation is largely outside the scope of regulation and oversight, despite its importance. For decades, the bioethics community has been unable to reach a consensus on whether there should be accountability in this work, as there is for other clinical activities that influence the care of patients. The American Society for Bioethics and Humanities, the primary society of bioethicists and scholars in the medical humanities and the organizational home for individuals who perform CEC in the United States, has initiated a two‐step quality attestation process as a means to assess clinical ethics consultants and help identify individuals who are qualified to perform this role. This article describes the process .